Functions of Fasciculation and Elongation Protein Zeta-1 (FEZ1) in the Brain - Andrés D. Maturana; Toshitsugu Fujita; Shun'ichi Kuroda (The Scientific World Journal)
Fasciculation and elongation protein zeta-1 (FEZ1) is a mammalian ortholog of the Caenorhabditis elegans UNC-76 protein that possesses four coiled-coil domains and a nuclear localization signal. It is mainly expressed in the brain. Suppression of FEZ1 expression in cultured embryonic neurons causes deficiency of neuronal differentiation. Recently, proteomic techniques revealed that FEZ1 interacts with various intracellular partners, such as signaling, motor, and structural proteins. FEZ1 was shown to act as an antiviral factor. The findings reported so far indicate that FEZ1 is associated with neuronal development, neuropathologies, and viral infection. Based on these accumulating evidences, we herein review the biological functions of FEZ1.